The conditional effect of personal vote-seeking behaviors on MPs electoral performance: Evidence from an open-list PR system. (December 2021) - Poyet, Corentin
Abstract: Considerable research argues that voters reward personal vote-seeking behaviors. The expected electoral gain would be the primary driver of MPs' action. Nevertheless, empirical evidence is scarce, and the findings do not always match the theoretical expectations. This article examines the electoral impact of personal vote-seeking behaviors, arguing in favor of integrating party electoral performance into the models. I also propose a new measure of electoral performance based on the evolution of MPs electoral results. Drawing on data from Finland, the findings globally support the theoretical arguments. MPs benefit from personal vote-seeking behaviors, primarily when their party improves its results. The findings have important implications for our knowledge of the personal vote and, more generally, the personalization of politics.